2020
DOI: 10.1007/s15010-020-01468-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum amyloid A in patients with COVID-19

Abstract: Objective To investigate the prognostic value of serum amyloid A (SAA) in the patients with Corona Virus Disease 2019 (COVID-19). Methods The medical data of 89 COVID-19 patients admitted to Renmin Hospital of Wuhan University from January 3, 2020 to February 26, 2020 were collected. Eighty-nine cases were divided into survival group (53 cases) and non-survival group (36 cases) according to the results of 28-day follow-up. The SAA levels of all patients were recorded and compared on 1 day after admission (befo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 15 publications
(12 reference statements)
8
36
3
1
Order By: Relevance
“…Three studies were prospective [ 29 , 41 , 52 ], 51 retrospective [ 20 28 , 30 34 , 36 39 , 42 46 , 48 51 , 53 , 54 , 57 60 , 62 , 63 , 65 , 66 , 69 76 , 78 , 80 , 81 , 83 86 ], while 13 did not specifically declare the study design [ 23 , 35 , 40 , 47 , 55 , 56 , 61 , 64 , 67 , 68 , 77 , 79 , 82 ]. Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were prospective [ 29 , 41 , 52 ], 51 retrospective [ 20 28 , 30 34 , 36 39 , 42 46 , 48 51 , 53 , 54 , 57 60 , 62 , 63 , 65 , 66 , 69 76 , 78 , 80 , 81 , 83 86 ], while 13 did not specifically declare the study design [ 23 , 35 , 40 , 47 , 55 , 56 , 61 , 64 , 67 , 68 , 77 , 79 , 82 ]. Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 ...…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 , 65 67 , 86 ]. Endpoints included disease severity based on current clinical guidelines (31 studies, 46%) [ 22 , 24 , 28 , 32 , 33 , 35 , 36 , 38 , 39 , 44 47 , 49 52 , 54 , 56 , 58 , 64 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 83 ], survival (19 studies, 28%) [ 20 , 23 , 26 , 30 , 31 , 34 , 42 , 53 , 59 – 62 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…In COVID-19, plasma SAA has recently been suggested as a biomarker of severity; patients with high initial levels of SAA levels were more likely to have poor computed tomography imaging 40 . SAA was suggested as a predictor of prognosis in patients with COVID-19, being significantly higher in non-survivors versus survivors, with a higher sensitivity relative to CRP 41 . In the present study, no difference was observed between survivors and non-survivors for any protein identified in HDLs from COVID-19 patients; this may be due to the small number of patients (4 survivors and 4 non-survivors).…”
Section: Discussionmentioning
confidence: 98%
“…Between first symptoms and hospitalization (days) 8 [2][3][4][5][6][7][8][9][10][11] Between hospitalization and ICU admission (days) 3 [2][3][4][5] Severity scores at admission SAPSII, median [IQR] 44 [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] SOFA, median [IQR] 6 [5][6][7] Treatments during ICU stay Norepinephrine, n (%) 6 (75)…”
Section: Timing Of Hospitalizationmentioning
confidence: 99%
“…We measured pro-inflammatory and metabolic markers associated with inflammation in serum samples from positive and negative individuals. We measured SAA (serum amyloid A protein) [34,35], CRP (C-reactive protein) [36][37][38][39] and ferritin [38,40,41]. These proteins are markers of pathogen-driven pulmonary inflammation, embolism, and disseminated intravascular coagulation, all characteristics of COVID-19, and therefore predictors of adverse health outcomes.…”
Section: Saa Crp and Ferritin Markers Of Covid-19 Are Higher In Pomentioning
confidence: 99%